The role of the digital world and its effect in realization of the objectives of the Islamic economy: a juristic study - دور العالم الرقمي وأثره في تحقيق أهداف االقتصاد اإلسالمي: دراسة فقهية - Saleh, Abdulmajid Obaid Hasan; Zakariyah, Habeebullah (IIUM Press, International Islamic University Malaysia, 2019)
E-commerce and the digital world are among the initiatives that are addressed by many contemporary researchers. This study seeks to find out how important the digital world, e-commerce and informatics are in achieving the goals of the Islamic economy. This study also aims to develop the concept of the digital world, and to determine whether the digital world is in line with the objectives of the Islamic economy. This research uses the descriptive and inductive approaches to trace the higher goals and objectives of the Islamic economy, and then incorporate them into the study area, and demonstrate the advantages of the digital economy. This research concludes that the digital world does not contradict the Shariah objectives related to wealth. These are represented in the following: breaking down the barriers; standardizing the market, the speed and ease of information exchange between consumers; reducing the distance between producers and consumers which helps in making the concept of full competition in the market consistent with the objectives of the Islamic economy in the clarity of the contract and its safety from gharar at the level of its construction; the prohibition of monopoly; the promotion of trade and activating the principle of supply and demand based on product quality; incorporation of the concept of coexistence and human exchange; reverence for science and knowledge; and encouragement for renewal and development by expanding the area of ijtihad in the drafting of contracts. This all leads to speediness, quality and mutual benefits, which are in line with the Shari`ah and the objectives of wealth observed in this sector.